Poor Education and Unemployment Implications for Youth Crimes in Nigeria - Angel Olofinbiyi, Sogo; Balgobind Singh, Shanta (International Journal of Criminology and Sociology, 2022)
Research on the correlation between education, occupation and criminality among the youth has grown both in length, and complexity in the last two decades. Using a mixed-method analysis, this study concurs that educational and occupational variables are significant determinants of criminal propensities but maintains two sides of the same coin by contending that the level of educational attainment of the youth does not grossly influence their involvement in criminal activities, whereas it draws on occupational attainment as a strong factor for the pervasive involvement of youth in criminality. Taking evidence from Nigeria, the study recommends policies that will review and implement youth entrepreneurial development, educational re-orientation and creation of more job opportunities, as a life-changing instrument against crime.